Steroid Resistant Takayasu Arteritis - Dasgupta, Malay Kumar; Das, Sabyasachi; Guha, Debasree (Journal of Nepal Paediatric Society, 2013)
Takayasu’s arteritis (TA), a chronic inflammatory disease affecting the aorta, its branches and the pulmonary arteries has become increasingly recognized as a worldwide entity, with a variable spectrum of disease expression. Here in a case of paediatric Takayasu arteritis affecting purely the arch of aorta and it’s branches that was steroid resistant. DOI: http://dx.doi.org/10.3126/jnps.v33i2.7113 J Nepal Paediatr Soc. 2013; 33(2):144-146